Surface Modification of Paper-Based Analytical Devices Using Polymer Inclusion Films as Optical Sensors for The Detection of Cu(II) Ions in Water - Ajung, Oktaviani; Tambaru, David; Lapailaka, Titus; Kadang, Luther; Nitti, Fidelis (Universitas Nusa Cendana, 2025)
This study presents the development of a microfluidic paper-based analytical device (µPAD) modified with a polymer inclusion film (PIF) for the detection of Cu(II) ions in aqueous samples. The PIF formulation comprised of polyvinyl chloride (PVC), bis(2-ethylhexyl)phosphoric acid (D2EHPA), and Aliquat-336, while sodium zincon salt served as the colorimetric reagent. The optimization was conducted by systematically varying several key parameters such as PIF composition and volume, reaction time, sample volume, and sample pH. The resulting color intensity was digitally quantified using smartphone, and the results were validated against UV–Vis spectrophotometry as the reference method. The optimized conditions were established at a composition of 50% PVC, 30% D2EHPA, 20% Aliquat-336 and 0.1% zincon, with a PIF volume of 20 µL, a reaction time of 40 minutes, a sample volume of 30 µL, and an optimal pH of 5. Under these conditions, the µPAD demonstrated excellent analytical performance, exhibiting strong linearity (R² = 0.9993), high precision (0.36%), good accuracy (0.368%), recovery rates between 98.18% and 102.44%, a limit of detection (LOD) of 0.143 mg/L, and a limit of quantification (LOQ) of 0.476 mg/L. Furthermore, selectivity assessments indicated that D2EHPA effectively reduced interference from Zn(II) ions, confirming the robustness of the developed sensing platform.